Regional wage differentials in Portugal: Static and dynamic approaches - Pereira, João (2011)
This work aims to study regional wage differentials from both a static and a dynamic perspective. The usual Blinder and Oaxaca static decomposition does not provide clear information about the factors which explain changes in regional wage differentials over the years. To overcome this problem the Juhn, Murphy and Pierce decomposition is employed. The paper analyses the case of Portugal for 1995 and 2002. The results show that, although the changes in the interregional wage inequality were small, they were caused by important and counteracting factors.